The expression is 5^(n-1)
Here is your answer:
Therefore the answer is "65/88."
Hope this helps!
We know that if we had
8/6=2/2 times 4/3=1 times 4/3=4/3
find common factors in top and obttom
factor
48a^4-16a^2-32=(16)(a-1)(a+1)(3a^2+2)
8a^2-8=8(a-1)(a+1)
so we have

(2)(3a^2+2)=6a^2+4
answer is 6a^2+4
Answer:

Step-by-step explanation:
We are given that:

And we want to find F'(0).
First, find F(x):
![\displaystyle F'(x) = \frac{d}{dx}\left[ f(3x)]](https://tex.z-dn.net/?f=%5Cdisplaystyle%20F%27%28x%29%20%3D%20%5Cfrac%7Bd%7D%7Bdx%7D%5Cleft%5B%20f%283x%29%5D)
From the chain rule:
![\displaystyle \begin{aligned} F'(x) &= f'(3x) \cdot \frac{d}{dx} \left[ 3x\right] \\ \\ &= 3f'(3x)\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7D%20F%27%28x%29%20%26%3D%20f%27%283x%29%20%5Ccdot%20%5Cfrac%7Bd%7D%7Bdx%7D%20%5Cleft%5B%203x%5Cright%5D%20%5C%5C%20%5C%5C%20%26%3D%203f%27%283x%29%5Cend%7Baligned%7D)
Then:

In conclusion, F'(0) = 15.